The mental condition survey of sand volleyball athletes from Kalimantan Selatan province during the match of POMNAS XVIII 2023 - Rakha Shema Alghahitza Ramiro Rap'i; Herita Warni; Rahmadi Rahmadi (PHEDHERAL, 2024)
This research is based on the importance of athletes' mental toughness in competitions. This research aims to determine the mental state of South Kalimantan Province's sand volleyball athletes when competing. By using quantitative descriptive research. As a quantitative study using a questionnaire/questionnaire. The sampling technique used random sampling, with the population and research subjects being athletes from South Kalimantan Province totaling 12 athletes. To analyze research data, percentage descriptive statistics were used. Based on research findings, it can be concluded that mental toughness is very important in controlling volleyball players' motivation to persist and view failure as a learning opportunity to take better steps next. Apart from that, anxiety and self-confidence also have an impact on the mental toughness of the South Kalimantan Province sand volleyball players' performance when competing.